THE IMPLEMENTATION OF EXTENSIVE LISTENING AND ITS EFFECT ON THE STUDENTS' LISTENING SKILL - Mahmudah, Memi (2015)
This study attempts to investigate the effect of exposure to spoken English by implementing the extensive listening procedure (Field, 2009) to the students' listening skills and also the students' attitude towards listening activities in general and also the implementation of extensive listening . The participants of the study were students in the eleventh grade of Senior High School in Bandung Barat. This study used a quasi experimental study and the data were collected by giving pre-test and post-test to the experimental group, which were given some instructions to implement the extensive listening procedure, and the control group, which were given selective listening procedure. The difference between the groups was tested by using the t-test in the SPSS. The students attitude towards the implementation of extensive listening was investigated by giving questionnares to the students. From the result of the tests it was found that there was a significant difference between the experimental and the control group. This was indicated by the value of t observed with the equal variances assumed is 2.367 which is higher than the value of t in the critical table (1.684) for df = 39. The significant difference can also be seen from the value of sig (two tailed) which is 0.023 which is lower than 0.05. The analysis of the questionnaires also found that most students responded positively to the implementation of extensive listening even though there were some students who also found that the listening materials were difficult. It can be concluded that exposure to English materials by implementing the extensive listening could have positive effect to the student' listening skills. Thus, it is recommended that teachers should encourage students to do the extensive listening, because the more students are exposed in English listening materials the more they get better in understanding the language. Key words: Extensive listening, listening skills. Penelitian ini bertujuan untuk menyelidiki efek Extensive Listening terhadap kemampuan siswa dalam menyimak, dan juga pendapat siswa tentang aktifitas menyimak secara umum dan juga tentang penerapan Extensive Listening. Partisipan dalam penelitian ini adalah siswa kelas sebelas di sebuah SMA di Bandung Barat. Penelitian ini menggunakan metode kuasi eksperimental dan datanya diperoleh dengan cara memberikan pre-test dan post-test kepada kelompok eksperimental, yang diberikan instruksi untuk menerapkan Extensive Listening. Perbedaan antara 2 kelompok ini diuji dengan menggunakan t-test dalam SPSS. Sikap siswa terhadap penerapan Extensive listening diteliti dengan cara memberikan kuisioner pada siswa. Dari hasil analisis ditemukan bahwa terdapat perbedaan yang cukup signifikan antara kelompok eksperimental dan kelompok kontrol. Hali ini dapat dilihat dari nilai t (2.367) yang lebih tinggi dari nilai t dalam tabel (1.684) untuk df = 39. Perbedaan dapat juga dilihat dari nilai α yaitu 0.023 yang mana nilai tersebut lebih rendah dari 0.05. Dari analisis kuisioner juga ditemukan bahwa kebanyakan siswa merespon secara positif terhadap penerapan Extensive Listening meskipun ada beberapa siswa yang menganggap materi listening terlalu sulit. Dapat disimpulkan bahwa pemberian materi Bahasa Inggris dengan menerapkan Extensive Listening dapat memberikan efek positif pada kemampuan menyimak siswa. Oleh sebab itu, direkomendasikan bahwa guru-guru harus mengajak siswa untuk menerapkan Extensive listening, karena semakin banyak siswa mendapatkan materi listening, semakin mudah juga bagi mereka dalam memahami materi Bahasa Inggris. Key words: Extensive listening, listening skills.